2015
DOI: 10.5194/aab-58-107-2015
|View full text |Cite
|
Sign up to set email alerts
|

Sea buckthorn pomace supplementation in the finishing diets of pigs – are there effects on meat quality and muscle fatty acids?

Abstract: Abstract. In the present study, the effect of sea buckthorn pomace (SBP) supplementation (concentrations of 0, 4, 8 and 12 %; intervention duration of 4 or 8 weeks) on finishing performance, meat quality parameters, and fatty acid and vitamin C contents in muscle of German Landrace pigs was assessed. Supplementation with SBP did not negatively affect growth performance and slaughter quality traits of pigs. The overall meat quality including nutrient composition (protein, fat, water), meat colour and pH value w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 14 publications
(20 reference statements)
2
22
1
Order By: Relevance
“…Fatty acid composition is an important factor in the nutritional quality of meat and adipose tissue and as such has long been a subject of study in meat science receiving considerable attention due to its important role in human health (Furman et al, 2010). For these reasons, the proper composition of fatty acids in meat and fat has become an important issue from the standpoint of consumers, nutritionists, and food technologists (Nuernberg et al, 2015). Fatty acid composition is influenced by genetic factors, including breed differences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fatty acid composition is an important factor in the nutritional quality of meat and adipose tissue and as such has long been a subject of study in meat science receiving considerable attention due to its important role in human health (Furman et al, 2010). For these reasons, the proper composition of fatty acids in meat and fat has become an important issue from the standpoint of consumers, nutritionists, and food technologists (Nuernberg et al, 2015). Fatty acid composition is influenced by genetic factors, including breed differences.…”
Section: Discussionmentioning
confidence: 99%
“…Ulbricht and Southgate (1991) suggested that the ratio of PUFAs to SFAs (P : S) should be at least 0.4 and the atherogenic index lower than 0.5. Consumers are becoming increasingly interested in safe, tasty, healthy and regional-origin meat products produced under eco-friendly, animal-friendly and sustainable (resource-conserving) conditions (Nuernberg et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the current human diet is usually already rich in fats, especially saturated and n-6 polyunsaturated, and there is also a need to balance the n-6/n-3 fatty acid intake for prevention of chronic diseases, it is particularly essential to evaluate the fatty acid profile in daily eaten foods, such as meat products [17,19]. Yet, the composition of meat fat depends on various factors, such as the individual characteristics of the animal (age, sex, species, breed) and its diet [17,20,21]. Proper selection of raw materials can therefore have a positive effect on the fatty acid profile.…”
Section: Introductionmentioning
confidence: 99%
“…However, a lot of research has been conducted on carcass traits at different slaughter weights (Beattie et al, 1999;Latorre et al, 2004;Correa et al, 2006;Serrano et al, 2008), which confirms the influence of this factor. A shorter duration of organism growth determines the changes in the proportions of carcass tissue composition, especially the content of muscle (Lefaucheur et al, 1991;Skiba et al, 2012;Nuernberg et al, 2015). The explanation for these observations may be the overly small half-carcass mass variation within groups.…”
Section: Discussionmentioning
confidence: 99%